In and Out of the Sound Studio: Introduction - McCartney, Andra; Waterman, Ellen (Intersections, 2006)
In the introduction to this special issue of Intersections, Andra McCartney and Ellen Waterman reflect on In and Out of the Sound Studio, an inter-university ethnographic research project funded by the SSHRC between 2001 and 2005. The research team studied ideas and practices of contemporary Canadian soundmakers, aiming to address the relative invisibility and inaudibility of women, and thinking about ways in which sound technologies and practices are gendered. In their essay, the authors discuss the relationships found among the terms gender, sound, and technology in terms of terminology, aesthetics, mentoring, methodology and theory. Contributions by McCartney, Diamond, Laplante, Labrosse, Marsh, and Bosma are discussed.